2010
DOI: 10.1177/1460458210380521
|View full text |Cite
|
Sign up to set email alerts
|

Using no-show modeling to improve clinic performance

Abstract: 'No-shows' or missed appointments result in under-utilized clinic capacity. We develop a logistic regression model using electronic medical records to estimate patients' no-show probabilities and illustrate the use of the estimates in creating clinic schedules that maximize clinic capacity utilization while maintaining small patient waiting times and clinic overtime costs. This study used information on scheduled outpatient appointments collected over a three-year period at a Veterans Affairs medical center. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
138
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 24 publications
(34 reference statements)
8
138
0
1
Order By: Relevance
“…We are not aware of any studies investigating a role for NLP in measuring appointment adherence. [19][20][21][32][33][34][35][36][37][38][39][40] Thus, our work highlights a novel method using NLP for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of any studies investigating a role for NLP in measuring appointment adherence. [19][20][21][32][33][34][35][36][37][38][39][40] Thus, our work highlights a novel method using NLP for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…No-shows result in fragmented continuity of care, reduce access for other patients in the practice, and decrease provider productivity. [8][9][10][11][12][13][14][15][16] Studies in primary care and specialty clinics have demonstrated that staff phone calls are an effective intervention for reducing no-shows. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, this convincing work is difficult to apply, because staff phone calls are timeconsuming and costly.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,30,31 Nevertheless, even in practices with low baseline no-show rates, the risk of no-show is heterogeneous-that is, some patients are more likely of noshows than others. 9,10,28,29,[32][33][34] Prior work has effectively demonstrated that no-shows are predictable; validated models can accurately predict the likelihood that a patient will fail to keep a scheduled appointment. 9,[35][36][37][38] Subspecialty clinics have made use of the predictability of no-shows by integrating predictive modeling to target interventions to those at high risk of no-show.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate the effects of no-shows and cancellations, clinics can try to influence patient behavior or modify their scheduling strategy [79]. Patient behavior can be influenced by education, reminders, and financial rewards or penalties.…”
Section: Strategies To Impact Patient No-show and Cancellation Behaviormentioning
confidence: 99%